Ecological Factors Affecting Waterfowl Production on Three Man-Made Flowages in Central Wisconsin - Baldassarre, Guy A. (University of Wisconsin-Stevens Point, College of Natural Resources, 1978)
Ecological factors affecting waterfowl production on 3 man-made flowages in central Wisconsin were studied from April 1975 through August 1976. Production of near flight-aged ducklings (0.23-0.29/acre; 0.57-0.72/ha) was 3-9 times lower than that reported from the productive waterfowl marshes in southern Wisconsin. Low production was directly related to poor soil and water fertility. Soils were organic, acidic, not well decomposed, and low in nutrient content. Water was very soft, moderately acidic, and also low in nutrients. Poor flowage fertility depressed invertebrate populations which were comparatively of low quality and somewhat unavailable during the breeding and brood rearing season. Wetland vegetation was often characterized by low quality waterfowl food plants. Suitable nesting cover was not a limiting factor for mallards (Anas platyrhynchos) or Canada geese (Branta canadensis) but may restrict blue-winged teal (Anas discors) due to the lack of preferred dry grassland cover. Artificial nest destruction in the limited grassland habitat available (dikes) was high (96.7 percent). Duck production was greatest on B Flowage where better quality habitat prevails. Water was more fertile and shallow while plant and invertebrate foods were of better quality and availability. Deeper water, particularly on D Flowage, may be seriously limiting food availability to migrating and breeding puddle ducks. Management recommendations included water level manipulations designed to increase invertebrate abundance, food availability, and to recharge marsh fertility.